Evaluation of the Burdening on the Czech Population by Brominated Flame Retardants - Logerová, Hana; Tůma, Petr; Stupák, Michal; Pulkrábová, Jana; Dlouhý, Pavel (International journal of environmental research and public health, 2019)
The completed environmental study was concerned with assessing the exposure of the Czech population to polybrominated diphenyl ethers (PBDEs). Simultaneously, the levels of polychlorinated pollutants such as polychlorinated biphenyls (PCBs) and chlorinated diphenyl ethanes (DDTs) were also monitored. The pollutant levels were newly measured in solid fat tissue removed during plastic surgery. A total of 107 samples of fat were taken from 19-76-year-old volunteers. A total of 16 PBDE congeners were determined, of which only six occur in more than 38% of fat tissue samples. The total PBDE level attains an average value of 3.31 ng/g, which is 25% less than was measured in 2009. On the other hand, there was an increase in the levels of two PCB congeners, which was caused by an increase of the total PCB concentration from level of 625.5 ng/g, published in 2009, to the current level of 776 ng/g. The level of DDTs decreased and currently has a value of 467.4 ng/g, which is about 24% lower than in 2009. The contamination of obese middle-aged women in Czechia by more modern types of pollutants, such as PBDEs, is incomparably lower than that by PCBs and DDTs and is also decreasing in time.
Keywords: polybrominated diphenyl ethers; tuková tkáň; polychlorované bifenyly; mass spectrometry; Humans; retardanty hoření; lidé středního věku; Female; Aged; vystavení vlivu životního prostředí; dospělí; mladý dospělý; Flame Retardants; PCBs; gas chromatography; senioři; lidé; human fat tissue; látky znečišťující životní prostředí; flame retardants; Adult; Environmental Pollutants; ženské pohlaví; Male; Middle Aged; Czech Republic; Environmental Exposure; Young Adult; DDTs; Česká republika; mužské pohlaví; Adipose Tissue; Polychlorinated Biphenyls